Keseragaman penggunaan istilah-istilah perakaunan dalam laporan tahunan korporat di Malaysia - Abdul Rahman, Azhar; Mohd Nasir, Mohd Herry; Ismail, Shahifol Arbi (Universiti Utara Malaysia, 2006)
This study investigates the practice,usage and uniformity of accounting terms in the Malay version of the annual reports of Malaysian companies. A total of 91 annual reports were selected as samples.This study only focuses on 20 items in the balance sheet. Frequency, Chi-square and Kruskal-walis tests were employed to analyze the data.The findings showed that 15 out of the total terms studied are consistent with the ones suggested by the Malaysian Accounting Standard Boards (MASB).The results also showed that 14 out of the total terms studied are used uniformly across the industries. This study is important as it pioneers the study on the usage of the Malay language in finanacial reports.